KESIAPSIAGAAN MASYARAKAT TERHADAP BAHAYA LAHAR DINGIN GUNUNG MERAPI - Ramanditya Wimbardana (Bumi Lestari Journal of Environment, 2013)
AbstractAfter the 2010 eruption of Mt. Merapi, ten million cubic meter of volcanic material ravagedsettlements, infrastructures, and agriculture areas where it located at downstream area of13 rivers. Lahar becomes threat for 1 million people who live on the flanks because it canflows along the rivers anytime. However, community is still standing in their hamlets andrefuses housing relocation plan that suggested by the government. This research aims toexplore community preparedness for lahar threat in Mt. Merapi flanks. Understanding thisinformation will help policy makers for disaster risk reduction that community empowermentis needed to cope with it. Research method applied with 244 questioners distribution tohousehold who live in four hamlets in Kali Putih riverside and lahar prone area. Analyticalmethod used statistic approach with descriptive analysis. Many households have preparedsome action in order to protect them from lahar despite they have lack of information howto face lahar. This study recommends capacity building forhousehold level and communitylevel by local government and NGOs in lahar prone area of Mount Merapi.